PENEGAKAN HUKUM OLEH KEPOLISIAN TERHADAP PENYALAHGUNAAN TINDAK PIDANA SENJATA API BAGI MASYARAKAT SIPIL DI WILAYAH HUKUM KEPOLISIAN RESOR KOTA PEKANBARU - Diana, Ledy (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2016)
Pekanbaru improvement and increasing economic growth make this city as a citythat is the target of a criminal offense, no exception misuse of firearms. Problems misuse offirearms by civil society both ordinary people and the perpetrators Legal region PekanbaruCity Police today remains a serious concern. In fact, Indonesia itself has long been applyingthe Emergency Law on Firearms in implementing law enforcement misuse of firearms. Butthe misuse of firearms do people still frequently occur , with a mode different crime. Thus theneed for improved and efforts to overcome these problems by the police , especially its policeresort city of Pekanbaru.The purpose of this thesis, namely: First, Knowing enforcement bythe police against the crime of misuse of firearms for civil society in the region PekanbaruCity Police Law. Second, what are the constraints Police in law enforcement against criminalacts of misuse of firearms for civil society in the region Pekanbaru City Police Law Third toovercome the constraints of law enforcement against criminal acts of misuse of firearms forcivil society in the region Pekanbaru City Police Law.This research is a law researchsociological research that want to see the correlation between law and society,usinginterviews in Pekanbaru City Police and also the study of literature.Keywords : Law Enforcement - Pekanbaru Police - Firearms